Caracterização do processo de produção da Scheelita no município de Currais Novos/RN - Félix, José Felipe Lino (Universidade Federal Rural do Semi-Árido, 2020)
Mining is an activity of great economic and social value, which helps a lot in the country's development. The discovery of the Brejuí Mine in the city of Currais Novos / RN was a major milestone for the recognition and development of ammunition that had an economy focused on livestock and cotton. With an exploration, and an ore production in the city became known nationally and worldwide, or the munich started to have new advances in the progress of the exploration and production of the scheelite. New houses, buildings, church, villages, theme parks, job creation, all these factors were driven by Mineradora Tomaz Salustino. The present work was developed in two stages, the first part was made a bibliographic research to deepen the studies on the theme of scheelite production, the second was a field research carried out in the MTS, being made based on a questionnaire with emphasis in describing or step by step the production of the wheel executed in the mine, since the extraction of the mineral inside the tunnels. Looking for information on the age and education of employees, the benefits brought to the city through the exploitation of ore, the amount of waste consumed, large-scale production, use of waste. So, conclude that the production process is quite similar to the past years, and the amount of brushes is reduced compared to the period of the period is relatively good, because the number of employees is very reduced nowadays, a mine produces a lot of waste that does not prove useful in any MTS, recognizing some factor
Keywords: Scheelita; Produção do minério; Mina Brejuí; Scheelita; Ore production; Brejuí Mine; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA